For a fertile future - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Fertiliser Strategies. FAO. 1999. 114 pp. ISBN 9251043515 US$ 14 15.40 (See other FAO reference for address)